Analisis Faktor-Faktor Berpengaruh Terhadap Rendahnya Penerapan Kode Etik Profesi Insinyur Pada Pembangunan Ruang Poliklinik RSUD dr. Soeroto Kabuapten Ngawi - Hariyanto, Agus (2012)
The research aim is to analyze the factors that affect the poor implementation of the code of engineer's ethics at Polyclinic Construction dr. Soeroto Hospital of Kabupaten Ngawi. The reason of this research is due to the deviation of the higher trend in the construction field. This trend is a reflection of the increasing violation to the code of engineer's ethics. The research is a descriptive one with qualitative method in order to describe systematically, factually, and accurately relationship among studied phenomena. Location of the research is selected purposively by considering that the project was one with highest value at that time and many digressions in its construction had been found and became popular in the Kabupaten Ngawi so that the digression case was proposed to Corruption Crime Court. Data is collected by using interview, observation, and documentation. Interview is performed with informants from the hospital, executive contractor, supervision consultant, and other tender participants. Observation is conducted in passive-participative manner. Documentation is performed by collecting data from report of examination results of Badan Pemeriksa Keuangan (BPK) of East Java Province, report of examination results of Inspektorat of Kabupaten Ngawi about construction of polyclinics room of dr. Soeroto General Hospital of Kabupaten Ngawi. Based on the results of this research, the analysis of four factors of the low implementation of the code of engineer's ethics at polyclinic Construction et dr. Soeroto hospital of Kabupaten Ngawi are : commitment among key persons, human resources, public policy and the conflict interest among actors. Low commitment factor was seen in the executive contractor who handed over the work to other party without any clear documents. Problem of human resource factor was found in the project owner in which low quantity and inappropriate of technical employees were found. Problem of policy factor emerged because there was no clear rule regulating about ethical code of engineer profession in Kabupaten Ngawi so that there was no protection for project owner and no sanction threat against executive contractor who violates ethical code of engineer profession in Kabupaten Ngawi. Furthermore, conflict of interest emerged between project owner and supervision consultant. There was power backing the executive contractor so that the project owner was less resolutely supervising works of the executive contractor because the project owner was subordinate of the power, whereas the supervision consultant tended to allow the executive contractor with reason of his company existence. Based on analysis performed in the research, the four factors affecting low implementation of ethical code of engineer profession in construction of polyclinic room of dr. Soeroto General Hospital of Kabupaten Ngawi were proved, namely: commitment factor, human resource factor, policy factor and conflict of interest. Whereas, recommendation for local government of Kabupaten Ngawi in attempts of reinforcing ethical code of engineer profession is law enforcement against any digression in commitment between actors or in policy that is taken. The technical professionalism of human resources skills shouid improve. This improvement can be done through the proccess of auction. It should be implemented from the performance to maintenance of the work. Commitment strengthening of every actor such as: signing of integrity pact by engineers. Finally, implementation of ethical code of engineer profession is expected to protect the service user, especially local government of Kabupaten Ngawi.